The Blood Component Iron Causes Neuronal Apoptosis Following Intracerebral Hemorrhage via the PERK Pathway - Wu, Muyao; Gao, Rong; Dang, Baoqi; Chen, Gang (Frontiers in Neurology, 2020)
PERK signaling pathway plays an important role in neuronal apoptosis after Intracerebral hemorrhage (ICH). ICH can cause the release of blood components into the brain. However, which component in the blood plays a major role still unclear. This study was designed to investigate the activation of the PERK pathway in different blood components after ICH and explore which components have major relationships with neuronal apoptosis. Eighty-five Sprague–Dawley rats were used to establish an ICH model. Western blot (WB) and immunofluorescence (IF) were used to evaluate the expression of the PERK pathway. TUNEL staining, FJC staining and neurological score were used to evaluate neuronal apoptosis and necrosis after ICH. The results showed that protein levels of p‐PERK and p‐eIF2α were upregulated following ICH with the injection of Fe3+ and Fe2+ after 48 h. Then, deferoxamine (DFX) was used to study the roles of Fe3+ in ICH through the PERK signaling pathway. The results showed that injection of DFX reversed increasing protein levels and prevented neuronal apoptosis. Thus, iron plays an important role in ICH through the PERK signaling pathway. Furthermore, the reduction of iron demonstrates neuroprotective effects in ICH. This suggests that targeting intervention of the iron and PERK pathway could be an effective treatment strategy to improve ICH prognosis.